2020
DOI: 10.1177/0022034520979644
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Atomization from Rotary Dental Instruments and Its Mitigation

Abstract: Since the onset of coronavirus disease 2019, the potential risk of dental procedural generated spray emissions (including aerosols and splatters), for severe acute respiratory syndrome coronavirus 2 transmission, has challenged care providers and policy makers alike. New studies have described the production and dissemination of sprays during simulated dental procedures, but findings lack generalizability beyond their measurements setting. This study aims to describe the fundamental mechanisms associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 13 publications
6
57
0
Order By: Relevance
“…The concentration of log 3.25±0.59 TCID 50 /ml was measured in LS. This observation is in accordance with a recent paper, stating that mixing the introduced coolant with real saliva also requires consideration (Sergis et al 2020). In our case, with virus titration control in saline suspension and splatter collected directly at the USS, the concentration reduction was 0.87 log, which is near 10x dilution and goes perfectly with the ratio of virus suspension and irrigant flow.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The concentration of log 3.25±0.59 TCID 50 /ml was measured in LS. This observation is in accordance with a recent paper, stating that mixing the introduced coolant with real saliva also requires consideration (Sergis et al 2020). In our case, with virus titration control in saline suspension and splatter collected directly at the USS, the concentration reduction was 0.87 log, which is near 10x dilution and goes perfectly with the ratio of virus suspension and irrigant flow.…”
Section: Discussionsupporting
confidence: 93%
“…The EAV predominantly spreads via larger droplets (splatter) that, according to ballistic laws, reach the near surrounding area, as infected droplets consistently infected cells on plates up to the distance of 45 cm (16 th well) from the USS tip. These observations are in accordance with a recent review (Sergis et al 2020) stating that contaminants settle to a great extent on the operator’s dominant arm, eyewear, and chest of the patient, and to a lesser extent on the non-dominant arm and chest of the operator and assistant. To the best of our knowledge, this is the first proof of the contribution of an USS action to the spread of the virus via droplets to the environment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Researchers at Imperial College London and King's College London have measured and analysed aerosol generation during dental procedures and suggested changes to prevent contamination in the first place, to improve safety for both patients and the dental practice workforce. 1 They suggest that dentists avoid using dental drills that use a mixture of air and water as the abrasion coolants, and carefully select and control drill rotation speeds for those instruments that only use water as a coolant. Parameters have been identified that would allow some procedures such as dental fillings to be provided while producing 60 times fewer aerosol droplets than conventional instrumentation.…”
Section: Jason Leitch Webinarmentioning
confidence: 99%